Competition between translation initiation factor eIF5 and its mimic protein 5MP determines non-AUG initiation rate genome-wide. Issue 20 (18th September 2017) - Tang, Leiming; Morris, Jacob; Wan, Ji; Moore, Chelsea; Fujita, Yoshihiko; Gillaspie, Sarah; Aube, Eric; Nanda, Jagpreet; Marques, Maud; Jangal, Maika; Anderson, Abbey; Cox, Christian; et al.
Abstract: In the human genome, translation initiation from non-AUG codons plays an important role in various gene regulation programs. However, mechanisms regulating the non-AUG initiation rate remain poorly understood. Here, we show that the non-AUG initiation rate is nearly consistent under a fixed nucleotide context in various human and insect cells. Yet, it ranges from <1% to nearly 100% compared to AUG translation, depending on surrounding sequences, including Kozak, and possibly additional nucleotide contexts. Mechanistically, this range of non-AUG initiation is controlled in part, by the eIF5-mimic protein (5MP). 5MP represses non-AUG translation by competing with eIF5 for the Met-tRNAi-binding factor eIF2. Consistently, eIF5 increases, whereas 5MP decreases translation of NAT1/EIF4G2/DAP5, whose sole start codon is GUG. By modulating eIF5 and 5MP1 expression in combination with ribosome profiling we identified a handful of previously unknown non-AUG initiation sites, some of which serve as the exclusive start codons. If the initiation rate for these codons is low, then an AUG-initiated downstream ORF prevents the generation of shorter, AUG-initiated isoforms. We propose that the homeostasis of the non-AUG translatome is maintained through balanced expression of eIF5 and 5MP.